Stunting dan Absennya Hak Perempuan - Fotarisman Zaluchu; Irfan Simatupang (Inovasi, 2023)
Stunting is a global issue. Indonesia is one of the countries having a big burden on stuntingproblems in the Southeast Asian region and in the world. The stunting prevalence trend in Indonesiashows a decrease, yet it is dominated more by direct intervention to the children who are sufferersof stunting and who are not, less than 5 years old. The impact such as this is not permanentbecause the program does not involve the pregnant women or the mothers of those children, whoare the closest figures to every children. One of the stunting contexts that is being ignored all thistime is fulfilling the rights of sexual health and gender equality to mothers. Before having theirfamily, during pregnancy, and when raising their children, many women reproductive’s right areignored and even put aside. Finally, the optimal health of mothers and children less than 5 yearsold is never achieved. This paper discusses those rights and explains the relation with the stuntingproblems. As discussed in this paper, it is shows that the government is not successful in providingservices that fulfill women's rights. Many health services are in fact not impartial or eveninaccessible to women. Thus, the government actually contributes significantly to the non-fulfillment of women's rights. This paper recommends that efforts to reduce the prevalence ofstunting are not only from health perspective. Empowerment of women through women's groupsis important to put forward. It is also important for the government to fulfill the right to reproductivehealth through the reconstruction of norms in society through state institutions. In addition, thegovernment must ensure the fulfillment of health services that are stand on women’s side. Only bythis ways, stunting can be prevented in the future.Keywords: stunting, reproductive health right, gender, Indonesia